Optimization of triple transfection in adeno-associated virus gene therapy vector production - Selander, Ilona (My University, 2021)
Recombinant adeno-associated virus (rAAV) is a safe gene delivery vector that provides long-term transgene expression in non-dividing somatic cells. This study was conducted to set up a large-scale rAAV vector production method. A protocol for producing GFP-carrying rAAV vectors by transfection of three plasmids was optimized for adherent and suspension HEK293 cells. Production was implemented with suspension cells in the cultivation volume of 25 ml and with adherent cells on 6-well plates. Different plasmid DNA quantities, transfection reagent to plasmid DNA ratios, and plasmid molar ratios were tested with both cell lines. The maximum yield of 1011 viral vectors was obtained from 1 ml of clarified cell lysate with both adherent and suspension cell lines. Transfection reagent PEIpro to plasmid DNA ratio of 2:1 provided the highest rAAV yield with both lines. With suspension cells, the transfection of 1.5 μg plasmid DNA provided higher vector yield than 1 μg. The diameter and survival percentage of transfected cells were investigated with suspension cells. The results indicated that the cell diameter does not predict transfection efficiency, whereas very low survival rate predicts low vector yield. This study provided certain guidelines important for large-scale rAAV production.
Keywords: adeno-associated virus, rAAV, vector, triple transfection, transduction, plasmid production